1995
DOI: 10.1103/physrevb.52.11853
|View full text |Cite
|
Sign up to set email alerts
|

Resonant photoemission study on the boron 1sexciton of the wide-band-gap semiconductorc-BN

Abstract: The B 1s exciton spectrum of the wide-band-gap semiconductor c-BN has been studied by resonant photoemission spectroscopy. The core-exciton band is found with a binding energy of about 1.2 eV. The constant-initial-state spectra for the valence-band features indicate that the B 1s exciton is the intermediate state for the resonant photoemission from the valence band. A satellite is found below the lower valence band by the resonant photoemission at B 1s exciton. The energy distribution curves of the valence ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…However, the band calculations, which were carried out by means of local density approximation ͑LDA͒ and other methods, indicate smaller band gaps. [27][28][29][30][31][32][33][34][35][36] On the other hand, a quasiparticle band calculation is in good agreement with our result. The cBN band gap and valence bandwidths obtained by the present study are listed in Table I.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…However, the band calculations, which were carried out by means of local density approximation ͑LDA͒ and other methods, indicate smaller band gaps. [27][28][29][30][31][32][33][34][35][36] On the other hand, a quasiparticle band calculation is in good agreement with our result. The cBN band gap and valence bandwidths obtained by the present study are listed in Table I.…”
Section: Resultssupporting
confidence: 87%
“…The core exciton has been already observed by Fomichev et al 9 in TPY and by Shin et al in the total electron yield ͑TEY͒ spectra. 33 Shin et al measured the resonant PES and CIS ͑constant initial state͒ spectra around CE region, and found the strong resonance enhancement of the valence band structure at the CE structure. This fact also suggests that the CE is a core exciton structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These numerical values, with the exception of W, are estimated from experimental data. 8,9 The value of W is only an adjustable parameter and this choice will be discussed later. The values of V 0 and ⌫ c we adopted are consistent with the very small reflectance of the order of 10 Ϫ5 -10 Ϫ6 near the core-exciton resonance.…”
Section: ͑13͒mentioning
confidence: 99%
“…Carson and Schnatterly 7 found that both the exciton intensity and binding energy could be explained with a Wannier model. Recently, synchrotron radiation sources and measurement systems have been improved to the extent that Raman scattering spectra in the soft-x-ray region, 8 and the core-exciton structure in total photon yield ͑TPY͒ spectra, 9 have been observed. These are usually interpreted by conventional extensions of concepts established in the visible frequency region.…”
mentioning
confidence: 99%